Quality Attributes and Shelf-Life Estimation of Cassava Flour Incorporated Bakery Product (Biscuit) - Khatri, Sabin Bahadur; Acharya, Dev Raj (Himalayan Journal of Science and Technology, 2021)
Cassava (Manihotesculentacrantz) is not true cereals are largely grown all over the world. They are very important due to their excellent nutritional contents especially protein, crude fiber, and carbohydrates. Biscuits were prepared by mixing cassava and wheat flour. Six treatments were prepared by adding 10%, 20%, 30%, 40%, and 50% cassava flour with wheat flour (Sample B, C, D, E, and F respectively) along with controlled treatment of 100% wheat flour (A). The proximate composition of flours was analyzed and prepared biscuits were subjected to sensory evaluation and shelf-life estimation. The obtained data was analyzed statistically by Genstat Discovery Edition 3 (DE3), for Analysis of Variance (ANOVA) at a 5% level of significance. Statistical analysis showed that sensory parameters and overall acceptability of 80 parts wheat and 20 parts cassava flour incorporated biscuit was significantly superior to all biscuits formulations. The proximate results of the best product showed that moisture content, crude fat, crude protein, crude fiber, total ash content, and total carbohydrate were found 3.44±0.25%, 13.80±0.33%, 8.13±0.13%, 1.29±0.19%, 2.41±0.06%, and 70.99±0.50 (g/100g) respectively. The shelf life of the best product was estimated by analyzing acid value and moisture content of the product by using three different packaging materials biaxially polypropylene (BOPP), high-density polypropylene (HDPE), and polypropylene (PP) respectively. The shelf life of the best product (80-20) wheat and cassava flours was found to be satisfactory for 8 weeks. The projected shelf life was found high in polypropylene (PP) and high-density polypropylene (HDPE) for 13.5 and 17.81 weeks for acid value and moisture content respectively.